Soil loss and accumulation due to wind erosion north of Zacatecas (TERRA LATINOAMERICANA, 2023)
The continuous changes in the use of soil for agricultural and livestock activities, as well the geographical location on sites af fected by continuous wind currents, have caused changes in soil characteristics in a period of 40 years. To identify such changes, this study was performed in the north of the state of Zacatecas. The results of soil from 300 samples obtained in the laboratory analysis in 1976 were compared against an equal number of samples obtained in 2016. “Raster” images were generated by georeferencing the sampling sites and interpolating with “kriging”. The coinciding determinations between databases showed the dif ferences between them by overlapping both images. The wind erosion was estimated and the levels of erosion associated with the sites where the changes occurred. The image analysis shows a matching area where sand content and soil pH increased. Such surface represents 401 907 ha of 2 118 000 ha covered by the images, where calcium has decreased in 98% of the surface, as well as potassium (59%), organic matter (58%), magnesium (49%) and sodium (35%) in 40 years, identifying areas of accumulation and soil loss associated with values of wind erosion. The prevailing SW winds that cause wind erosion were identified with values from 8 to 32 Mg ha-1 in 100 209 ha of accumulation and 233 587 ha of losses in 40 years. Of the total identified, 199 753 ha are agricultural areas and 202 154 are for livestock use. The identification of areas should help define plans and public policies for technological intervention.
Keywords: pH changes; degradation; sand transport; prevailing wind